Intervensi Meditasi Perhatian Penuh: Cara Mengurangi Stres pada Atlet Bola Voli Junior - Qori Nur Hijah; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. In volleyball games, athletes often experience stress, which many internal and external factors can cause. This causes athletes to feel chaotic and unable to perform at their best. So, they often experience defeat in matches. This study aims to examine the effects of mindfulness meditation training on reducing stress in junior volleyball athletes. Materials and methods. The method used in this research is a pretest, posttest experimental method with a quantitative approach involving 14 Bandung Regency volleyball athletes. The instrument used in this study is a stress questionnaire. This study used an instrument in the form of a Depression Anxiety Stress Scales for Youth (DASS-Y) questionnaire, which is a tool to measure stress in children and adolescents. The treatment given is mindfulness meditation, which is done for four weeks. There are three sessions in one week, each lasting 15-25 minutes. The data obtained was then processed using SPSS 25. Data processing begins with descriptive statistics to summarize the data, followed by normality tests to ensure the data distribution was appropriate. Finally, we conducted hypothesis testing using a paired t-test to determine the effectiveness of mindfulness meditation training in reducing stress levels before and after the program. Results. The results showed that mindfulness meditation training significantly reduced the stress level of junior volleyball athletes, as evidenced by a decrease in the average stress score from 18.21 to 14.07 after treatment, with a difference of 5.20%. It can be concluded that mindfulness meditation intervention is one of the most effective psychological exercises to reduce stress in junior volleyball athletes. Conclusions. This study concludes that mindfulness meditation intervention is a way that influences reducing stress in junior volleyball athletes. This study suggests that more attention should be paid to the psychological condition of athletes and provide mental exercises such as mindfulness meditation when there are athletes who have indications of stress.